2022
DOI: 10.3989/mc.2022.01922
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on effect of colloidal nano-silica on the strength and durability characteristics of red mud blended Portland cement paste through tortuosity

Abstract: A novel binder system for cement-based composites depending upon the strength and durability characteristics is introduced in this study. The possibility of calcined red mud cement pastes with and without colloidal nano-silica (CNS) over Ordinary Portland Cement paste (OPC) at three W/B ratios (0.3, 0.4, 0.5) is evaluated. The optimum percentage of cement replacement by red mud (15%) was selected from compressive strength values of different cement replacements (5%, 10%, 15%, and 20%). Colloidal nano-silica (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…Athira and Shanmugapriya (2022) [91] investigated the potential of using calcined red mud cement pastes with and without colloidal nano-silica (CNS) at different (W/B ratios). They found that the incorporation of 1.5% CNS into red mud cement paste led to decreased water absorption at all W/B ratios, indicating that adding nano-silica can enhance the durability of cement-based materials.…”
Section: Water Absorptionmentioning
confidence: 99%
“…Athira and Shanmugapriya (2022) [91] investigated the potential of using calcined red mud cement pastes with and without colloidal nano-silica (CNS) at different (W/B ratios). They found that the incorporation of 1.5% CNS into red mud cement paste led to decreased water absorption at all W/B ratios, indicating that adding nano-silica can enhance the durability of cement-based materials.…”
Section: Water Absorptionmentioning
confidence: 99%